PENGARUH PENGGUNAAN FORMAT DOKUMENTASI KEPERAWATAN BERBASIS CHECKLIST TERHADAP MUTU DOKUMENTASI ASUHAN KEPERAWATAN - Udi Wahyudi; Sri Rejeki,; Sara Ulliya (Jurnal Keperawatan Notokusumo, 2017)
Background: The importance of nursing care documentation as a means of communication between health professionals in patient safety program (patient safety), requires the nurse to make nursing documentation in accordance with the quality standards of documentation. But in reality the implementation of the documentation of nursing care in hospitals is still much that is not in accordance with the standards of documentation, so it will affect the quality of documentation. This is because hospitals still use the nursing documentation in the form of a narrative format. Objective: This study aims to look at the effect of using the format of a checklist-based nursing documentation of the quality of nursing care documentation in inpatient hospitals KRT. Setjonegoro. Method: a quasi-experimental design or pre-experimental design with a draft posttest with controlled group. Sampling using random or random sampling. Samples used as many as 44 people were divided into 2 groups, ie 22 people as a group intervention or treatment and 22 people as the control group. Test analysis used to see the effect of using the format of a checklist-based nursing documentation on the quality of documentation is the simple linear regression statistical test. Results: Based on the simple linear regression test obtained t value (6.038) is greater than the value t table (1,725), and the smaller the p-value (0.000) of the value of ? (0.05). Conclusion: Research conclusion that there is the influence of the use of the format of checklist-based nursing documentation of the quality of nursing care documentation in inpatient hospitals KRT. Setjonegoro Wonosobo.